Investigating Corporate Social Responsibility (CSR) Initiatives on Consumer Buying Behavior: The Most Influential Factor (Journal of Governance and Development (JGD), 2012)
Corporate Social Responsibility (CSR) is a concept where companies integrate social and environmental concerns in their business operations and in their interaction with their stakeholders on a voluntary basis. A majority of the companies believe that the development of a CSR strategy can deliver real business benefits. Apparently, it has been shown that a company performing CSR successfully , not only benefits the community but gains more customers, increases employee productivity and the company’s profits. Despite increasing emphasis on CSR in the marketplace, little is known about the effects of CSR initiatives on consumers and which of the CSR initiatives are the most influential to the company. Thus, this paper aims to investigate the influence of CSR initiatives towards consumer buying behavior and to identify which initiatives will be the most influential factor towards consumer buying behavior. A sampling procedure based on the convenience sampling technique was employed. A total of 230 structured questionnaires were distributed, with 190 returned for analysis. The results showed that there are significant relationships between environmental, human and safety and health initiatives with consumer buying behavior and subsequently human initiative is shown to be the most influential factors among the independent variables. The implication of these findings shows that the aspects of human factor should be given consideration and priority in the practice of CSR due to the influence on consumer buying behavior.